A Qualitative Analysis of Innovative Teaching and Counselling Techniques to Foster Early Childhood Growth and Resilience - Rozikan, Muhamad; Adisti, Aprilian Ria (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This study examines the integration of innovative teaching and counseling techniques to promote early childhood growth and resilience, drawing on Constructivist Theory. Unlike previous research that examines these aspects separately, this study provides a holistic perspective. A descriptive, qualitative approach was employed in three kindergartens in Salatiga, Central Java, which were selected for their diverse educational practices. Fifteen experienced educators were purposefully chosen to ensure varied insights.Data collection included systematic observations and in-depth interviews. Observations, conducted over two weeks, documented teaching methods, counseling strategies, and educator-child interactions. Semi-structured interviews, lasting 30–60 minutes, further explored educators’ approaches and perceptions. The thematic analysis identified key patterns. Findings reveal that each kindergarten applied unique strategies. One integrated digital storytelling to enhance engagement, while another emphasized emotional regulation to foster resilience. Group activities facilitated collaboration and social learning. The study highlights how combining innovative teaching with adaptive counseling enhances cognitive, social, and emotional development. This study makes a unique contribution to early childhood education by demonstrating the effectiveness of integrating teaching innovations with counseling strategies. Recommendations emphasize the need for diverse teaching methods and adaptive counseling techniques to address various developmental needs, offering valuable insights for educators in enhancing children's resilience and growth.